THE PROPER TREATMENT OF DISTRIBUTION COSTS. - Castenholz, W. B. (The Accounting Review, 1927)
Abstract In a manufacturing business, according to the author's view, there are only two primary and fundamental activities, which should be made to embrace all operating factors and the costs attached to them, the two activities are those of production and distribution. Management and administration in a manufacturing business or in any other business, are not ends in themselves. In manufacturing the administrative function must concern itself either with problems of production or problems of distribution. Financial activities of an internal nature over which management has control must also be viewed as assisting production and distribution in the proportion that these two fundamental divisions utilize the funds of the business. It is generally admitted that modern cost accounting methods lead to an accurate knowledge of product cost, costs which express themselves in the various inventories of manufactured product, and, of course, in the inventories in process. Cost accounting methods also enable one to recognize and give effect to all the variable production factors that enter into the manufacture of a variety of goods.